2008
DOI: 10.1519/jsc.0b013e31817bd45d
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Responses to Resistance Exercise in Long-Term Trained and Untrained Middle-Aged Men

Abstract: This cross-sectional study compared hormonal responses to resistance exercise between trained and untrained men to investigate the adaptations of the endocrine system to long-term strength training in middle-aged men. Twenty-one middle-aged men were recruited for this study and matched into a strength-trained group (SG) (n = 10) and an untrained group (UG) (n = 11). In the SG, the individuals had practiced strength training for hypertrophy for at least 3 years. Upper- and lower-body muscle strength was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 34 publications
4
63
2
3
Order By: Relevance
“…Acute exercise-induced increases in T concentrations have been widely reported [13][14][15][16][17]. However, despite exercise being a commonly used first-line treatment for mild ageassociated T decrements [18,19], it remains unclear whether exercise can potentiate a reversal of the age-associated decline in systemic androgens.…”
Section: Introductionmentioning
confidence: 99%
“…Acute exercise-induced increases in T concentrations have been widely reported [13][14][15][16][17]. However, despite exercise being a commonly used first-line treatment for mild ageassociated T decrements [18,19], it remains unclear whether exercise can potentiate a reversal of the age-associated decline in systemic androgens.…”
Section: Introductionmentioning
confidence: 99%
“…endurance trained young males showed attenuated increases in hormone concentrations in response to exercise compared to resistance-trained individuals (Tremblay et al 2004). One study has compared hormonal responses to resistance exercise in middleaged strength-trained and untrained men (Cadore et al 2008). There were no differences in hormones between trained and untrained men at rest; however, untrained men demonstrated a significant increase in DHEA and cortisol in response to acute resistance exercise, where trained men did not.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that cortisol concentrations increase either immediately following commencement of exercise [28][29][30][31] or at 15 min into rest [32], with cortisol concentrations returning to baseline anywhere from 30 min [32] to 3 hours following commencement of exercise [31]. Larger increases in post-exercise cortisol concentrations and elongated cortisol recovery times were associated with highintensity exercise of a greater duration.…”
Section: Discussionmentioning
confidence: 99%